Guidelines for revalidating a process hazard analysis (CCPS guidelines series., 2023)
"This book is derived from the experience of many companies in the chemical and hydrocarbon processing industries, and presents demonstrated, concise, and common sense approaches for a resource-effective revalidation of process hazard analyses (PHAs). It includes flowcharts, checklists, and worksheets that provide invaluable assistance to the revalidation process. The new edition, now as a guideline, provides a complete and thorough update of the first book and will provide much needed and requested guidance on PHA Revalidations including evaluating Prior PHA Studies, Identifying an Appropriate Revalidation Methodology, Preparing and Conducting the Revalidation Study Sessions, and Documenting the Revalidation Study"--